Landscape evolution modelling in large, complex braided river the Brahmaputra: a case study of Majuli Island, North-East India - Gogoi, Prasujya (2018)
The River Brahmaputra is one of the largest rivers, ranking ninth in terms of mean annual discharge (19, 800 m3s-1). The river has a multi-channel, braided/anastomosed planform that changes frequently and exhibits rapid transformations in channel morphology. This research was set in the context of the River Brahmaputra near Majuli Island, Assam, India. Morphologically, this part of the river is very volatile, increased braiding intensity of the river is believed by many to be responsible for severe erosion in the southern part of Majuli Island. Therefore in this research, a medium-term morphological evolution and change are investigated, in a study reach of 40 km near southern part of Majuli Island, Assam. There is a limited number of morphological models that can model the landscape evolution of braided rivers. Beside this, there is high cost and difficulty in collecting the hydrological, hydraulic, morphometric and sediment data needed to run a 2D, physics-based model in a very large, complex braided river, particularly as data for such rivers is often sensitive and therefore classified. Therefore the best alternative for modelling complex, braided rivers with limited data availability is to use a form of simplified morphological model which is known as a reduced complexity model or RCM. The rcm model CAESAR-Lisflood was used in this research to model medium term channel evolution. New indices were developed to validate the rcm model which quantify lateral shifting of the thalweg (Thalweg Migration Index, TMI), braiding intensity (Modified Plan Form Index, MPFI), cross-sectional disposition of anabranch channels (Modified Flow Geometry Index, MFGI) and change in bar area (Bar Deformation Index, BDI). Trends and changes in the four braiding indices that were forecast by the C-L + models indicated that the Brahmaputra in the study reach is likely to remain volatile morphologically for the next two decades. Deposition in this reach is very likely to continue to exceed erosion, with net deposition increasing through time due to increased sediment inputs associated with greater monsoon runoff. The River Brahmaputra may widen its primary channel in response to increased runoff and net deposition and therefore the braiding intensity will most probably intensify. The thalweg channel may remain shifting northwards towards Majuli Island. The number of sandbars is likely to increase and rates at which sandbars are formed and deformed are likely to rise. The bank erosion and loss of floodplain may become more severe, especially in the southern part of Majuli Island.